Phenotypic and Genotypic Features of a Salmonella Heidelberg Strain Isolated in Broilers in Brazil and Their Possible Association to Antibiotics and Short-Chain Organic Acids Resistance and Susceptibility - Santin, Elizabeth; Hayashi, Ricardo Mitsuo; Wammes, Jessica Caroline; Gonzalez-Esquerra, Ricardo; Carazzolle, Marcelo Falsarella; Freire, Caio César de Melo; Monzani, Paulo Sérgio; Cunha, Anderson Ferreira da (Frontiers in Veterinary Science, 2017)
Salmonella enterica serovar Heidelberg (SH) is a human pathogen also found in broilers. A strain (UFPR1) has been associated with field reports of resistance to short-chain organic acids (SCOA) in broilers in the South of Brazil, but was susceptible to a Bacillus subtilis-based probiotic added in feed in a related study. This work aimed to (i) report clinical symptoms caused by SH UFPR1 in broilers, (ii) study its susceptibility to some antibiotics in vitro and (iii) SCOA in vivo; and (iv) relate these phenotypic observations with its genome characteristics. Two in vivo trials used 1d old chicks housed for 21d in 8 sterilized isolated negative pressure rooms with 4 battery cages of 12 birds each. Birds were challenged or not with 107 CFU/bird of SH UFPR1 orally and exposed or not to SCOA in a 2x2 factorial design. Zootechnical parameters were unaffected (P>0.05), no clinical signs were observed, and few cecal and hepatic histologic and immune-related alterations were seen, in birds challenged with SH. Formic and propionic acids added together in drinking water, formic and benzoic acids in feed (Trial 1), and coated calcium butyrate in feed (Trial 2) did not reduce the SH isolation frequencies seen in cecum and liver in broilers after SH challenge (P>0.05). SH UFPR1 was susceptible to amikacin, amoxicillin + clavulanate, ceftiofur, cephalexin, doxycycline and oxytetracycline; and mildly susceptible to ampicillin + sulbactam, cephalothin, ciprofloxacin, enrofloxacin and gentamycin in an in vitro MIC model using Mueller-Hinton agar. The whole genome of SH UFPR1 was sequenced and consisted of a circular chromosome, spanning 4760321 base pairs with 52.18% of GC-content encoding 84 tRNA, 22rRNA and 4427 protein-coding genes. The comparison between SH UFPR1 genome and a multidrug resistant SL476 strain revealed 11 missing genomic fragments and 5 insertions related to bgt, bgr and rpoS genes. The deleted genes codify proteins associated with cell cycle regulation, virulence, drug resistance, cellular adhesion and salt efflux which collectively reveal key aspects of the evolution and adaptation of SH strains such as organic acids resistance and antibiotic sensitivity, and provide information relevant to the control of SH in poultry.